Groundwater geochemistry in bench experiments simulating CO2 leakage from geological storage in the Newark Basin. (November 2015) - Yang, Qiang; Matter, Juerg; Takahashi, Taro; Stute, Martin; O'Mullan, Gregory; Clauson, Kale; Umemoto, Kelsey; Goldberg, David
Highlights: Bench experiments simulating continuous and one-time CO2 leakage were conducted. Mineral dissolution and trace element release were enhanced by CO2 injection. Elemental release was less for one-time injection than for continuous CO2 flow. Elemental release rates decreased with increasing pH, or decreasing p CO2 levels. Monitoring key major and trace elements and pH can help detect CO2 leakage. Abstract: To learn the effect of CO2 leakage on shallow drinking water aquifers, laboratory experiments were conducted to measure the chemical changes of aquifer water, in which the fine fraction of sedimentary rock from the Triassic Newark Basin Series were immersed. Elevated CO2 concentrations caused a decrease in pH, an increase in the concentrations of major ions including Ca, Mg, Si, K, and alkalinity, an enhanced dissolution of carbonate minerals, and an increase in the concentrations of trace elements including Mn, Fe, Be, Cr, Co, Cu, Zn, Rb, Zr, Cd, Sb, Ba, Pb, and U in water under both continuous CO2 flow and one-time injection batch experiments. The magnitude of concentration increase was significantly lower in batch experiments with one-time CO2 injection than in experiments with continuous CO2 flow, although less rigorous agitation was maintained in the batch experiment. The logarithmic elemental release rates of Ca, Mg, Si, Mn, Fe and Zn normalized by reactive surface area, when plotted together with those from field injection experiments, decreased with the increase of pH (or the decrease of log ( p CO2 )) following linear trends. The laboratory elemental release rates were 1-3 orders of magnitude higher than field injection experiment rates extrapolated to incubation pH conditions. Hydrogeochemical parameters including pH, major and trace elements, particularly Fe, Mn, Cd, Tl, and sulfate, can be used as early indicators for leakage detection and need to be monitored in compliance with the U.S. Environmental Protection Agency (EPA) drinking water regulations.